Peningkatan Keterampilan Menulis Karangan Narasi Dengan Menggunakan Model Pembelajaran Think Pair Share di Kelas V Sekolah Dasar - Fatinnisa, Lulu; Harni, Harni; Sukma, Elfia (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The purpose of this research is to describe the improvement of narrative writing skill by Think Pair Share models at grade V student of Elementary School. The type of research is PTK by using qualitative and quantitative approach. This research was conducted at SDN 10 Bandar Buat, Padang city with a total of 30 students consisting of 12 male students and 18 female students. The result of the narrative writing skill in the pre-writing at cycle I 76,3 increases on cycle II 91,6. The writing phase in the first cycle 69,6 increased in the second cycle 83,5, the post-writing phase cycle I 69,6 increases in cycle II 83.5.  Keywords: Writing,Narrative,Think Pair Share (TPS)